LINGUISTIC FEATURES OF TONGUE TWISTERS - Samakova М. (Vestnik Issyk-Kulʹskogo universiteta, 2025)
Tongue twisters significantly differ from other types of works in the didactic genre in terms of their linguistic structure. This article, in addition to pointing out the various ways of using linguistic tools in the system of tongue twisters, also notes that these words are often repeated, sentences end in grammatically similar forms, and are organized in the same rhythm. This is observed not only in rhythmic tongue twisters but also in all types of folk oral works. The syntactic structure of the language of tongue twisters, the use of words, their arrangement, intonational features of pronunciation, as well as the differences in genre compared to other types of works in the didactic genre, will be demonstrated using actual material. Works of the didactic genre have semantic functions of repetition. Repetition in tongue twisters creates a special rhythm that affects their semantic content in this stylistic aspect, forming a distinctive feature of the tongue twister, enhancing its sonority, artistic quality, and euphony. This linguistic structure, verbal repetition, is considered one of the main characteristics of the language of tongue twisters.